1999
DOI: 10.21236/ada361025
|View full text |Cite
|
Sign up to set email alerts
|

Inspections of Previously Monitored Coastal Structures.

Abstract: The study reported herein was conducted as part of the Monitoring Completed Navigation Projects (MCNP) Program, formerly the Monitoring Completed Coastal Projects Program. Work was carried out under Work Unit 11M-7, "Periodic Inspections." Overall program management for MCNP is accomplished by the Hydraulic Design Section of Headquarters, U.S. Army Corps of Engineers (HQUSACE). The Coastal and Hydraulics Laboratory (CHL), U.S. Army Engineer Waterways Experiment Station (WES), is responsible for technical and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They also found 33 broken dolosse cast in 1974. Bottin and Tolliver (1999) and Bottin et al (2004) found no additional breakage over the 1993 survey. However, their surveys were limited to casual observations from on-site and careful comparison with aerial photographs.…”
Section: Broken Armor Unit Surveymentioning
confidence: 91%
See 1 more Smart Citation
“…They also found 33 broken dolosse cast in 1974. Bottin and Tolliver (1999) and Bottin et al (2004) found no additional breakage over the 1993 survey. However, their surveys were limited to casual observations from on-site and careful comparison with aerial photographs.…”
Section: Broken Armor Unit Surveymentioning
confidence: 91%
“…Baseline surveys were reported. Melby and Turk (1995), Markle et al (1995), Appleton et al (1996), Bottin and Tolliver (1999), and Melby (2002) discussed continued monitoring of the dolosse under the Periodic Inspections work unit as well as monitoring specifically for the San Francisco District. Monitoring has included wave climate, dolos movement and breakage, stress measurement within selected dolosse, and coring of dolosse for strength tests.…”
Section: History Of Crescent City Dolos Monitoringmentioning
confidence: 99%
“…Results of the walking inspection and suggestions are summarized by Bottin and Tolliver (1999) as follows:…”
Section: Cleveland Harbor East Breakwater 1997 Periodic Inspections Wmentioning
confidence: 99%